Pengaruh Kemanfaatan, Kemudahan Keamanan, dan Fitur M-Banking terhadap Kepuasan Nasabah dalam Bertransaksi pada Bank Syariah Indonesia (Studi Kasus BSI KCP Sumenep) - Putri Amalia; Hastriana, Anna Zakiyah (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2022)
Customer satisfaction is the emotional response that customers feel when they enjoy the experience of using a product/service. In increasing customer satisfaction, the banking industry is required to provide m-banking facilities. Achievement of increased customer satisfaction can be influenced by various factors, including usability, ease of use, features, and security. The independent variable other than the feature variable is a variable derived from TAM theory. Therefore, the purpose of this research is to test and analyze the influence of these four factors on customer satisfaction at BSI KCP Sumenep. This research is a survey research with a quantitative approach. Data collection techniques in this study used a questionnaire. The research sample is the customers of Bank Syariah Indonesia KCP Sumenep, who use m-banking Bank Syariah Indonesia as many as 100 respondents. The type of sample is purposive sampling. The data analysis technique used multiple linear regression using SPSS version 22.0. The results of this study indicate that the usefulness, ease of use, features, and security of m-banking have a positive and significant effect both partially and simultaneously on customer satisfaction.